PENGARUH OLAHRAGA AEROBIK DAN PEMBERIAN PIL BESI TERHADAP STATUS BESI DAN TINGKAT KESEGARAN JASMANI REMAJA - Permaesih, Dewi; Rosmalina, Yuniar; Herman, Susilowati; Moeloek, Dangsina (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
THE IMPACT OF AEROBIC EXERCISE AND IRON TABLETS ON PHYSICAL FITNESS AND IRON STATUS AMONG ADOLESCENT. Background: Iron deficiency anemia (IDA), as measured by hemoglobin level below normal value, is the most prevalent micronutrient deficiency in Indonesia. IDA among adolescent has been shown in some studies not only affect health status but also on decreasing learning concentration and physical fitness. So far, iron supplementation has been shown to improve iron status effectively and theoretically may also improve physical fitness among high risk groups especially adolescent. Objectives: To determine the effect of aerobic exercise and iron supplementation on physical fitness and iron status among adolescent. Methods: The subjects were adolescent boys aged 13-19 years old suffering from IDA In three Islamic boarding schools (Pondok Pesantren). A total of 181 selected subjects were assigned into two groups. The intervention group received iron tablet and aerobic exercise 3 times a week, while the control group received only iron tablet 3 times a week for the period of 7 weeks. Variables included in the study were health status assessed by physical examination by medical doctor, hemoglobin concentration, serum transferrin level, and cardiovascular endurance which were assessed before and after the intervention. Cardiovaskular endurance was measured by time needed to run for the distance of 2400 meters. Results: The results showed that the prevalence of IDA among adolescent of Islamic boarding school was 40 percent. Hemoglobin concentration in the intervention group increased significantly (2.02 ± 1.26 gram/dL) compared to that in the control group (0.83 ± 0.93 gram/dL) Serum transferrin receptor decreased by -0.41 + 2.3 and -0.28 ± 4.9 ug/L in the intervention and control groups respectively. Cardiovaskular endurance was significantly better in the intervention group (1.9 ± 0.3 minute faster) compared to that in the control group (0.5 ± 0.3 minute slower) after the intervention. Conclusions: Iron supplementation and aerobic exercise regularly significantly improve iron status and physical fitness among adolescent. Keywords: Iron tablet, physical fitness, aerobic exercise